Clinical Characteristics of Personality and Conduct Disorders in Child Patients With Vasovagal Syncope: A Clinical Case-Control Study - Wang, Tao; Wang, Fang; Li, Yifei; Shi, Xiaoqing; Duan, Hongyu; Zhou, Kaiyu; Hua, Yimin (Frontiers in Pediatrics, 2021)
Objective: To analyze the clinical characteristics of abnormal personality and conduct disorders (CDs) pediatric patients with vasovagal syncope (VVS). Method: In this study, we recruited patients diagnosed with VVS at Children’s Heart Center from January 2018 to December 2020. Healthy children were recruited as controls. The Eysenck Personality Questionnaire-Child edition (EPQ-C) and Achenbach Child Behavior Checklist (CBCL) were used for the assessment. Result: 151 VVS patients and 151 healthy controls were included in this study. Compared with the control group, patients in the VVS group had a higher incidence of abnormal personality and were more prone to suffer from CDs. Moreover, pediatric patients with VVS suffered more events of syncope recurrence if they had CDs. Conclusion: Abnormal personality and CDs are common clinical characteristics in pediatric patients with VVS.